2016
DOI: 10.1037/fam0000148
|View full text |Cite
|
Sign up to set email alerts
|

Conflict, negative emotion, and reports of partners’ relationship maintenance in same-sex couples.

Abstract: The literature on relationship maintenance has focused primarily on the beneficial outcomes of maintenance, and, as a result, little is known about relational processes that may interfere with reports of partners' maintenance. The authors examine how daily conflict influences individuals' reports of their partners' maintenance, and how a constructive communication style buffers this influence by reducing negative emotion on conflict days. In a daily diary study of 98 same-sex couples in romantic relationships,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…Due to this, we cannot comment on whether the associations between negative affect and interpersonal problems observed herein are a result of general psychopathology, with a number of associations being especially relevant to and pronounced in BPD, or whether the associations would hold in healthy individuals as well. Based on previous studies with healthy samples, revealing positive associations between conflict and negative affect (Bolger & Schilling, 1991; Bolger & Zuckerman, 1995; Kennedy et al, 2002; Laurenceau et al, 2005; Ogolsky & Gray, 2015), we presume that the general pattern of effects we observed herein would hold in healthy participants, too. However, we expect this association would be weaker in a number of ways, because healthy participants should have a lower general affective reactivity and lower sensitivity to negative events.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Due to this, we cannot comment on whether the associations between negative affect and interpersonal problems observed herein are a result of general psychopathology, with a number of associations being especially relevant to and pronounced in BPD, or whether the associations would hold in healthy individuals as well. Based on previous studies with healthy samples, revealing positive associations between conflict and negative affect (Bolger & Schilling, 1991; Bolger & Zuckerman, 1995; Kennedy et al, 2002; Laurenceau et al, 2005; Ogolsky & Gray, 2015), we presume that the general pattern of effects we observed herein would hold in healthy participants, too. However, we expect this association would be weaker in a number of ways, because healthy participants should have a lower general affective reactivity and lower sensitivity to negative events.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have not assessed the relationship between disagreement and negative affect in a BPD sample, although a number of studies using nonclinical samples have examined this. Daily diary studies of romantic couples have found a positive association of relationship conflict with daily negative affect (Ogolsky & Gray, 2015), anger (Kennedy, Bolger, & Shrout, 2002), and anxiety (Laurenceau, Troy, & Carver, 2005). Furthermore, disagreements with a spouse or other adults were positively associated with same-day negative affect (Bolger & Schilling, 1991) and with next-day anger and depression (Bolger & Zuckerman, 1995), the latter only for participants high in Neuroticism, a trait common in those with BPD (Samuel & Widiger, 2008).…”
mentioning
confidence: 99%
“…This study also found positive relationship events such as outings and socializing with one's partner were associated with increased levels of relationship satisfaction. Furthermore, in a 14-day diary study of same-sex romantic couples, Ogolsky and Gray (2016) found that experiencing higher perceived levels of daily conflict was associated with lower levels of the evaluation of relationship maintenance.…”
Section: Ideal-partner Discrepancies and Relationship Events/experiencesmentioning
confidence: 99%
“…We added five additional terms that were not used in any search. These are terms we have seen used in LGBT health research: “same gender loving” [ 36 ], “same sex couple” [ 37 ], “same sex couples” [ 38 ], “sexual and gender minority” [ 39 ], and its plural version, “sexual and gender minorities.” This full list of 82 terms is presented below with bolded terms coming from the identified reviews and italicized terms added based on their use in the field.…”
Section: Resultsmentioning
confidence: 99%